22R‐ but not 22S‐hydroxycholesterol is recruited for diosgenin biosynthesis. (7th December 2021) - Zhou, Chen; Yang, Yuhui; Tian, Jingyi; Wu, Yihan; An, Faliang; Li, Changfu; Zhang, Yansheng
SUMMARY: Diosgenin is an important compound in the pharmaceutical industry and it is biosynthesized in several eudicot and monocot species, herein represented by fenugreek (a eudicot), and Dioscorea zingiberensis (a monocot). Formation of diosgenin can be achieved by the early C22, 16‐oxidations of cholesterol followed by a late C26‐oxidation. This study reveals that, in both fenugreek and D. zingiberensis, the early C22, 16‐oxygenase(s) shows strict 22 R ‐stereospecificity for hydroxylation of the substrates. Evidence against the recently proposed intermediacy of 16 S, 22 S ‐dihydroxycholesterol in diosgenin biosynthesis was also found. Moreover, in contrast to the eudicot fenugreek, which utilizes a single multifunctional cytochrome P450 ( Tf CYP90B50) to perform the early C22, 16‐oxidations, the monocot D. zingiberensis has evolved two separate cytochrome P450 enzymes, with Dz CYP90B71 being specific for the 22 R ‐oxidation and Dz CYP90G6 for the C16‐oxidation. We suggest that the Dz CYP90B71/ Dz CYP90G6 pair represent more broadly conserved catalysts for diosgenin biosynthesis in monocots. Significance Statement: This study reports that two independent enzyme evolutions between the monocot and eudicot species occur at the early C22, 16‐oxidation steps for diosgenin biosynthesis. Despite the independent evolutions, the C22‐hydroxylation in both species is highly constrained to be in an R‐configuration in diosgenin biosynthesis.